Knockout of EGFL6 by CRISPR/Cas9 Mediated Inhibition of Tumor Angiogenesis in Ovarian Cancer - Zhu, Wenhui; Liu, Chunyan; Lu, Tongyi; Zhang, Yinmei; Zhang, Simin; Chen, Qi; Deng, Ning (Frontiers in Oncology, 2020)
Tumour angiogenesis plays an important role in the progression and metastasis of ovarian cancer. EGFL6 protein is highly expressed in ovarian cancer and has been proposed to play an important role in promoting tumour angiogenesis. Here, a CRISPR/Cas9 system was used to knockout the EGFL6 gene in the ovarian cancer cell line SKOV3, using specific guide RNA targeting the exons of EGFL6. The knockout of EGFL6 markedly inhibited the proliferation, migration and invasion of SKOV3 cells, as well as promoted apoptosis of tumour cells. In the nude mouse model of ovarian cancer, knockout of EGFL6 remarkably inhibited tumour growth and angiogenesis. The transcript profile assays detected 4,220 differentially expressed genes in the knockout cells, including 87 genes that were correlated to proliferation, migration, invasion, and angiogenesis. Moreover, Western blotting confirmed that EGFL6 knockout downregulated the FGF-2/PDGFB signalling pathway. Thus, the results of this study indicated that EGFL6 could regulate cell proliferation, migration, and angiogenesis in ovarian cancer cells by regulating the FGF-2/PDGFB signalling pathway.